Pengaruh Gaya Kepemimpinan dan Penggunaan Teknologi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Nawakara Di Kota Padang - Arib Aufaa M; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to determine and try to analyze the Influence of Leadership Style and Use of Technology on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Nawakara in Padang City. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of PT. Nawakara in Padang City. The results of the study found that there is a positive and significant influence between leadership style on job satisfaction. There is a positive and significant influence between the use of technology on job satisfaction. There is a positive and significant influence between leadership style on employee performance. There is a positive and significant influence between the use of technology on employee performance. There is a positive and significant influence between job satisfaction and employee performance. Job satisfaction mediates the influence of leadership style on employee performance. Job satisfaction mediates the influence of technology use on employee performance.